Difusi Model Live Commerce Tiongkok dalam Ekosistem Shopee Live dan Implikasinya terhadap Kompetensi Bahasa Mandarin Vokasional di Sektor E-Commerce Indonesia - Mei Lisa; Elly Romy; Wenny; Kevin Utama (Jurnal Ekonomi Bisnis Manajemen Prima, 2026)
Digital transformation has accelerated the rise of live commerce as a major innovation within the global e-commerce ecosystem, with China emerging as a leading pioneer whose practices have increasingly shaped other markets, including Indonesia. This study investigates the diffusion and adaptation of the Chinese live commerce model through Shopee Live in Indonesia, examines the effects of live commerce stimuli on Generation Z consumers’ purchasing behaviour, and explores the structural implications for vocational Mandarin language competencies in cross-border e-commerce. Adopting a quantitative descriptive–explanatory design, the study employs the Stimulus–Organism–Response framework and the Elaboration Likelihood Model to explain consumer decision-making processes. Data were collected via an online questionnaire administered to 112 Indonesian Generation Z consumers who actively use Shopee Live and were analysed using descriptive and explanatory statistical methods. The findings demonstrate that live commerce stimuli—particularly price promotions, real-time interaction, and host persuasion—significantly influence purchase intention and impulsive buying behaviour, with persuasive effects operating predominantly through the peripheral route. Furthermore, the results reveal a strong interconnection between Shopee Live and cross-border supply chains dominated by Chinese suppliers. This indicates that the diffusion of the live commerce model extends beyond shaping digital consumption patterns to restructuring cross-border business interactions. Consequently, the study underscores the growing strategic importance of vocational Mandarin language competencies that are practical, industry-oriented, and culturally sensitive. It concludes that vocational Mandarin proficiency constitutes a critical component of human resource development in Indonesia’s e-commerce sector amid the intensification of cross-border digital economic integration.